DEF6 is associated with the translational initiation regulating protein synthesis of eIF4E, 4E-T and PABP and colocalises with eIF4E and PABP in the immunological synapse - Alsayegh, Maha (2018)
DEF6 is an atypical guanine nucleotide exchange factor (GEF) for Rho GTPases Rac1 and Cdc42, which is highly expressed in mature T cells. DEF6 is recruited to the immunological synapse (IS) following phosphorylation by LCK in response to T cell receptor (TCR) stimulation during inflammation. In resting Jurkat T cells, DEF6 has been known to associate with polysomes and under cellular stress conditions to form cytoplasmic granules colocalising with mRNA decapping enzyme subunit 1 (DCP1), a marker of P-bodies. Hence DEF6 has been linked to mRNA regulation, which includes mRNA translation initiation and repression by P-body formation. To elucidate the structural requirements for P-body localisation of DEF6, N-terminal truncation mutants lacking either the C-terminal coiled coil domain or the pleckstrin homology (PH) domain in conjunction with the coiled coil domain were established and coexpressed with DCP1 in COS7. Both GFP-tagged mutant DEF6 proteins spontaneously colocalised with DCP1 indicating that the N-terminal end of DEF6 is sufficient for P- body association and that the coiled coil domain facilitates a confirmation that masks the N-terminal end of DEF6. Exchange of serine and/or threonine residues in the C- terminal end with either phosphomimic or phosphosilent amino acids resulted in formation of GFP-DEF6 aggregates or granules, respectively. While GFP-DEF6 granules partly overlapped with DCP1, GFP-DEF6 aggregates appeared to trap DCP1. In resting Jurkat cells endogenous DEF6 associated with nascent mRNA translation and colocalised with eukaryotic translation initiation factor 4E (eIF4E) as well as poly A binding protein (PABP). eIF4E and the eIF4E-binding protein 4E-T but not PABP were shown to interact with DEF6 in vitro. Moreover, siRNA-mediated knockdown and ectopic overexpression of DEF6 in Jurkat cells established a positive correlation of DEF6 expression and eIF4E, PABP and 4E-T protein expression. RT-PCR revealed that the alteration in expression of these proteins was not due to transcriptional regulation and inhibition of protein degradation pathways could not rescue downregulation of eIF4E. Colocalisation of DEF6 with eIF4E and PABP but not with 4E-T was also observed in the IS upon TCR-mediated signalling. Together these results strongly suggest that DEF6 is involved in active mRNA translation in resting and activated Jurkat T cells controlling the expression of components of the translational initiation complex as well as P-bodies.